SOSIALISASI PELAYANAN PUBLIK BERBASIS WEBSITE PLAVON MELALUI AKUN INSTAGRAM @Dispendukcapilsidoarjo - Sil Viyah Wanda Hamidah; Julyanto Ekantoro; Fitria Widiyani Roosinda (INTELEKTUAL ( E-Journal Administrasi Publik dan Ilmu Komunikasi ), 2022)
This research is a research on how the Plavon website-based public service socialization on the Instagram account @Dispendukcapilsidoarjo. This study aims to analyze how socialization of public services is carried out through agency Instagram accounts with all the advantages and disadvantages that exist on Instagram social media. This study uses a qualitative descriptive research method by describing the current state of the subject and research object based on the facts that have been collected. This study also used observational data collection techniques and direct interviews with the public relations division, especially in the Sidoarjo Dispendukcapil data base. The results of this study indicate that the socialization of public services based on the Plavon website carried out by the Sidoarjo District Population and Civil Registry Service through the institution's official Instagram account, namely @Dispendukcapilsidoarjo, is running as expected, this can be seen by the large number of people who know information about online services from the Plavon website. dukcapil through the agency's Instagram account. So that the community can take care of the required population administration documents independently.